A Review of Gear Fault Diagnosis Using Various Condition Indicators - Sharma, Vikas; Parey, Anand (Procedia engineering, 2016)
Plentiful work has been done for condition monitoring (CI) and fault diagnosis of fixed-axis gearboxes. However, still it is found that articles citing condition indicators for fault diagnosis of gearboxes are less in quantity, in academic journals, conference proceedings and technical reports. The specialty of condition indicators is to provide accurate information regarding the condition of various components at different levels of damage (initial, heavy or growing). Here, these indicators are addressed domain-wise and their characteristics are stated. The objective of this paper is to review and encapsulate this literature to provide a wide and good reference for researchers to be utilized. The structure of a fixed-axis gearbox is briefly introduced. The unique behaviors and fault characteristics of fixed-axis gearbox is recognized and studied. Investigations on the basis of statistical indicators are also summarized based on the adopted methodologies. Lastly, open problems are stated and further research prospects pointed out.